Design and Analysis of Electromechanical Controlled Globoidal Cam System - Ru Yan; Jujiang Cao; Yansong Liu; Jinsheng Liang (Jixie chuandong)
Due to its great advantages of high speed， reliability and transmission accuracy， the globoidal cam mechanism is widely used in various transfer mechanical equipment. In order to promote the research and development of intelligent manufacturing of basic components， and meet the needs of customized production， the design method of mathematical model of electromechanical controlled globoidal cam system is presented. Then， it is applied to the turning and lifting device of globoidal cam manipulator， and the dynamic characteristics and kinematic characteristics of the manipulator are analyzed. The research findings show that the electromechanical control globoidal cam system is stable， and the dynamic response is fast by adjusting the control parameters， and the motion characteristics are obviously improved， which meets the design requirements. The research provides a theoretical basis for expanding the application field of globoidal cam mechanism， lays a foundation for the development of the intelligent globoidal cam system.